The Influence of Academic Stress on Academic Burnout among Middle School Students in Guangdong - Yongmei, Hou; Dan, Wen (Advances in Social Sciences Research Journal, 2022)
Objective To explore the characteristic of academic stress and academic burnout, and analyze the impact of academic stress on academic burnout among middle school students in Guangdong Province, China. Methods A stratified cluster sampling method was used to select 1011 students from 6 middle schools in Guangdong province. Academic Stress Scale for Middle School Students (ASSMSS) and Academic Burnout Scale for Middle School Students (ABSMSS) were used to investigate them. Results ⑴ The total scores of ASSMSS and ABSMSS were (60.86±9.31) and (231.43±37.54), respectively. ⑵ The students with rather serious, serious, general, light academic burnout accounted for 13.60%, 20.53%, 24.43% and 41.44%, respectively. The students with serious, general and light academic stress accounted for 66.32%, 3.81% and 29.87%, respectively. ⑶ the result of multivariate stepwise linear regression showed that the scores of competitive stress, task requirement stress, frustration stress and expectation stress were positively correlated with the total score of ABSMSS (β=.258-.459，all P <.001). Conclusions The academic stress and academic burnout of middle school students in Guangdong are rather serious. Academic stress may be an important influenced factor of academic burnout.